Development and validation of a novel endoplasmic reticulum stress-related lncRNA prognostic signature and candidate drugs in breast cancer - Cai, Jiehui; Ji, Zeqi; Wu, Jinyao; Chen, Lingzhi; Zheng, Daitian; Chen, Yaokun; Zhang, Xinkang; Xie, Wanchun; Huang, Jieying; Chen, Manqi; Lin, Ru; Lin, Weixun; et al. (Frontiers in Genetics, 2022)
Breast cancer (BC), the most common malignancy in women, has a high cancer-related mortality. Endoplasmic reticulum stress (ERS), a response to the accumulation of unfolded proteins, has emerging roles in tumorigenesis, including invasion, metastasis, immune escape, etc. However, few studies have focused on the correlation between ERS with long non-coding RNAs (lncRNAs) in BC. We attempted to construct an ERS-related lncRNA prognostic signature, and study its value in BC from tumor mutational burden (TMB), tumor immune microenvironment (TIME), cluster, clinical treatment and so on. In the present study, transcriptomic and clinical data of BC patients were extracted from The Cancer Genome Atlas (TCGA) database. Correlation test, Cox regression analysis, least absolute shrinkage and selection operator (LASSO) method were performed to determine an ERS-related lncRNA prognostic signature. Survival and predictive performance were analyzed according to Kaplan-Meier curves and receiver operating characteristic (ROC) curves, while nomogram and calibration curves were established. Then, it was enrichment analysis that were performed to study the functions and biological processes of ERS-related lncRNAs. TMB and TIME were also analyzed to assess mutational status and immune status. Additionally, by consensus cluster analysis, we compared differences among tumor subtypes. Drug sensitivity analysis and immunologic efficacy evaluations were performed together for further exploration. We identified a novel prognostic signature consist of 9 ERS-related lncRNAs. High-risk patients had worse prognosis. The signature had good predictive performance as an independent prognostic indicator and was significantly associated with clinicopathological characteristics. Enrichment analysis showed that metabolic pathways were enriched in high-risk patients, while immune pathways were more active in low-risk patients. Low-risk patients had lower TMB, higher immune scores and stronger immune functions. Cluster analysis clarified cluster 2 had the most active immune functions and was sensitive to more drugs, which may have the best clinical immunological efficacy. Clinical efficacy evaluation revealed patients in the low-risk group may benefit more from chemotherapy, targeted therapy and immunotherapy.The novel signature has significant clinical implications in prognosis prediction for BC. Our study clarifies that there is potential connection between the ERS-related lncRNAs and BC, which may provide new treatment guidelines for BC.